VOLUNTARY ABANDONMENT IN SERBIAN CRIMINAL LAW AND MACEDONIAN CRIMINAL LAW (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
Pursuant to Article 32 of the Serbian Criminal Code, voluntary abandonment of the commission of a criminal offence exists when the perpetrator who attempted to commit a criminal offence voluntarily abandons or withdraws from the commission of the criminal act, or prevents the occurrence of legal consequences. As indicated in the definition of the concept of voluntary abandonment in criminal law, there are two essential legal requirements which must be cumulatively met: a) the criminal offense was attempted, and b) the perpetrator voluntarily abandoned the intended commission of the criminal act or prevented the occurrence of harmful consequences. The voluntary abandonment of the commission of a criminal offence is one of the legal grounds for possible exemption from criminal liability and punishment. The competent court has the authority to  render a decision on this matter, which means that the court may or may not exempt the offender from punishment when the aforesaid legal requirements for the application of this institute have been cumulatively satisfied. In this article, the authors analyze the legal nature of voluntary abandonment as a criminal law institute, compare its regulation in the Serbian and the Macedonian criminal law, and discuss some cases from the judicial practice in the Republic of Serbia. The aim of the paper is to point out to the significance of applying the legal institute of voluntary abandonment in the process of combating crimes because this institute has a direct impact on the  awareness of the criminal offenders about the importance of preventing the completion of criminal acts and the occurrence of harmful consequences, even when they have been attempted. It is ultimately important in terms of both special and general prevention of crimes.
Keywords: criminal law, voluntary abandonment, legislation, judicial practice.